Pendekatan Non-Litigasi dalam Penyelesaian Kekerasan Rumah Tangga Pada Masyarakat Aceh Timur - Jamadon, Jamadon; Zubir, Zubir; Fahriansah, Fahriansah (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
Domestic violence remains a significant issue in Aceh, largely influenced by the prevailing patriarchal culture and the limited protection available for victims. This study aims to examine the forms of domestic violence occurring within communities in East Aceh and evaluate its impacts on victims in physical, psychological, and social dimensions. Furthermore, the research analyzes the out-of-court resolution processes involving the roles of customary institutions, community leaders, and village governments. Employing a descriptive qualitative approach, data were collected through in-depth interviews with victims, perpetrators, and stakeholders involved in resolving domestic violence cases. The findings reveal various forms of domestic violence, including physical, psychological, sexual, and economic violence, with diverse impacts on victims depending on the social context of each village. Out-of-court resolutions are primarily facilitated through customary mediation, emphasizing a family-centered approach to prevent further conflict escalation. This study contributes to the literature on the role of customary conflict resolution systems in addressing domestic violence. It also highlights the need for more systematic and inclusive strategies to ensure justice for victims and reduce the prevalence of domestic violence in a sustainable manner.